Utilization of E-Government in Mail Administration Management at the General Section of the Regional Secretariat of Cirebon Regency - Sobirin, Sobirin; Wulandari, Sri (ann4publisher@gmail.com, 2026)
Background. Advances in information and communication technology (ICT) have driven digital transformation in the government sector through e-government policies aimed at delivering more transparent, accountable, effective, and efficient public services. Aims. This study examines the use of the e-government system in managing incoming and outgoing letters in the General Section of the Regional Secretariat of Cirebon Regency. This research aims to analyze the use of the Srikandi application, the level of user adoption, and the obstacles encountered during its implementation. Methods. This research employs a qualitative approach, with data collected through interviews, observations, and documentation. Conclusion. The results show that implementing e-government (through an electronic mail management system) can improve administrative efficiency and the speed of mail disposition; however, several obstacles remain, including limited human resources, insufficient training, and infrastructure constraints. Implementation. One form of e-government implementation in the Cirebon Regency local government is the use of the Integrated Dynamic Archive Information System (Srikandi) application to manage mail administration in the General Section of the Cirebon Regency Regional Secretariat.